ANALISIS IMPLEMENTASI DASHBOARD MONITORING AKTIVITAS TASK MENGGUNAKAN INTEGRASI CLICKUP API DAN N8N BERBASIS WEB DENGAN METODE PROTOTYPE - Andini Widi Bahrani; Ahmad Syazili (Lembaga Pengembangan Kinerja Dosen, 2026)
Project management applications are widely used to support team collaboration and task management. However, monitoring task activities directly through these platforms can be difficult because information is spread across multiple menus. This study aims to analyze the implementation of a web-based task activity monitoring dashboard integrated with ClickUp API and n8n. The system was developed using the Prototype method and provides project information such as task activities, project statistics, team productivity, overdue tasks, and automatic notifications through WhatsApp, Telegram, and Gmail. The results show that the system can display project information in real time and simplify monitoring activities through a single integrated dashboard. In addition, the notification feature helps users receive project updates more quickly and efficiently. Therefore, the system can support project monitoring and improve information delivery within a collaborative work environment.